Effect of heat stress on buffaloes under different shelter strategies - SETHI, R K; BHARADWAJ, A; CHOPRA, S C (The Indian Journal of Animal Sciences, 2013)
Effect of heat stress under different shelter strategies was observed in 16 lactating Murrah buffaloes in June and July when the ambient temperature ranged from 26°C to 45°C. In each randomly divided groups 4 animals were kept under 4 shelter propositions, viz (i) covered shed with sides closed, (ii) shed and given 2 showers at 1100 hr and 1500 hr, (iii) Lied undertree shade from 8 A M to 5 P M and (iv) exposed to direct sun rays and given 2 showers at the above timings. Animals in all the groups were provided ad lib. chaffed sorghum and maize fodder, and 3 kg concentrate per day and free access to drinking water. Pulse rate, respiration rate and rectal Temperature differed significantly among groups and parily order. Least-squaremeans and standard crrors fat the above traits during the cool hours were 60.4±0.3, 29.7±0.5 and 100.7±0.30 respectively. Highest increase in pulse rate (8.6), respiration rate (36.0) and rectual temperature (2.6°C) was observed in group 4 which was exposed to direct sunlight followed by Ihe group kept inside the shed. The latter group however expressed grealer increase in physiological parameters in the evening hours probablydue to The heating up of The enclosure. Groups 2 and 3 were more comfortable as was evident from their physiological response. Change in milk yield in the 4 groups differed significantly. Group 3 exhibited least adverse change in body parameters and milk production.